Implementasi pendidikan karakter untuk mencapai mutu pendidikan di SMP N 4 Satu Atap Pakis Kabupaten Magelang - Suhada, Imam; Supriyoko, Supriyoko (Journal of Education Policy and Management Studies, 2024)
The purpose of this study is to describe the implementation of caharacter education curricullum in the context of achieving quality education which includes implementation strategies, the relationship of character education with the quality of education and the role of pricipals and the teachers in student character building in Primary school Satu Atap Pakis Magelang. This research was a descriptive qualitative study. Data sources were obtained from in-depth interviews with 4 informants and 5 additional informants. Source of supporting data obtained from observation and documentation. Data collection techniques by interviewing, observing and documenting. Data from interviews, observations and documentation were analyzed descriptively. The data analysis technique in this study used by reducing data, displaying data and verifying research data. As for the test of the validity of the data of this study, namely the extension of observation, increasing perseverance, triangulation and member check.The results of the study indicated that the character education implementation strategy includes the integration of building character values in all subjects and teaching and learning activities both intra-extracurricular, character education through routine habituation, stakeholder involvement and the existence of building character values ( religious values, honesty, love for peace, hard work, creative, respect for achievement, communicative, fond of reading, environmental care, discipline, tolerance, responsibility, democratic, independent, national spirit, self-confidence and social care) in school. There was a close relationship between character education and quality of education as evidenced by the achievements obtained by students both academically and non-academically. The role of principals and teachers includes policy makers, motivators, and role models. There needs to be an increase in stakeholder involvement and communication in building character education values. In addition, there is need to improve the quality of the implementation of integration of activities in character education at SMPN 4 satu atap Pakis Magelang.